Efficacy of adjunctive nebulized colistin in critically ill patients with nosocomial carbapenem-resistant Gram-negative bacterial pneumonia: a multi-centre observational study. (October 2021) - Feng, Jia-Yih; Peng, Chung-Kan; Sheu, Chau-Chyun; Lin, Yu-Chao; Chan, Ming-Cheng; Wang, Sheng-Huei; Chen, Chia-Min; Shen, Yi-Cheng; Zheng, Zhe-Rong; Lin, Yi-Tsung; Yang, Kuang-Yao; ,
Abstract: Objectives: To investigate the association between adjunctive nebulized colistin and treatment outcomes in critically ill patients with nosocomial carbapenem-resistant Gram-negative bacterial (CR-GNB) pneumonia. Methods: This retrospective, multi-centre, cohort study included individuals admitted to the intensive care unit with nosocomial pneumonia caused by colistin-susceptible CR-GNB. Enrolled patients were divided into groups with/without nebulized colistin as adjunct to at least one effective intravenous antibiotic. Propensity score matching was performed in the original cohort (model 1) and a time-window bias-adjusted cohort (model 2). The association between adjunctive nebulized colistin and treatment outcomes was analysed. Results: In total, 181 and 326 patients treated with and without nebulized colistin, respectively, were enrolled for analysis. The day 14 clinical failure rate and mortality rate were 41.4% (75/181) versus 46% (150/326), and 14.9% (27/181) versus 21.8% (71/326), respectively. In the propensity score-matching analysis, patients with nebulized colistin had lower day 14 clinical failure rates (model 1: 41% (68/166) versus 54.2% (90/166), p 0.016; model 2: 35.3% (41/116) versus 56.9% (66/116), p 0.001). On multivariate analysis, nebulized colistin was an independent factor associated with fewer day 14 clinical failures (model 1: adjusted odds ratio (aOR) 0.59, 95% CI 0.37–0.92; model 2: aOR 0.37, 95% CI 0.21–0.65). Nebulized colistin was not associated independently with a lower 14-day mortality rate in the time-dependent analysis in both models 1 and 2. Conclusions: Adjunctive nebulized colistin was associated with lower day 14 clinical failure rate, but not lower 14-day mortality rate, in critically ill patients with nosocomial pneumonia caused by colistin-susceptible CR-GNB.